2021
DOI: 10.20944/preprints202109.0345.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Societal Burden of Endometriosis on Women: a Metaethnography

Abstract: Background: Endometriosis affects between 1% to 10% of women worldwide; it is associated with a significant burden on the woman, her relationships, productivity, mental health, family and society. Aim:To contribute to the current understanding of the impact of endometriosis on women’s lives by integrating qualitative research findings to explore the illness experiences of women living with endometriosis. Study design:Synthesis of qualitative data using Britten’s meta-ethnography.Methods:Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Diagnosis can take seven years on average after symptom onset [4] but ranges from four to 11 years [5], suggesting a major impact on women's psychological well-being both before diagnosis and after [6]. Indeed, a recent meta-ethnography in which the illness experience of endometriosis patients across the globe was investigated stressed the negative impact of this disease on many aspects of life [7]. Speci cally, the authors found that women with endometriosis encountered a multitude of problems including infertility, di culty in maintaining intimate relationships (both emotional and physical) with their partners, psychological distress, negative emotions that could lead to suicidal ideation, low sense of self, low productivity at work, increased absenteeism, poor academic performance, social isolation, and low quality of life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis can take seven years on average after symptom onset [4] but ranges from four to 11 years [5], suggesting a major impact on women's psychological well-being both before diagnosis and after [6]. Indeed, a recent meta-ethnography in which the illness experience of endometriosis patients across the globe was investigated stressed the negative impact of this disease on many aspects of life [7]. Speci cally, the authors found that women with endometriosis encountered a multitude of problems including infertility, di culty in maintaining intimate relationships (both emotional and physical) with their partners, psychological distress, negative emotions that could lead to suicidal ideation, low sense of self, low productivity at work, increased absenteeism, poor academic performance, social isolation, and low quality of life [7].…”
Section: Introductionmentioning
confidence: 99%